Pengaruh Silika Terhadap Membran Blend Kitosan-Polivinil Alkohol-Litium Sebagai Membran Elektrolit Baterai Ion Litium - Riska Novitasari; Siang Tandi Gonggo; Suherman Suherman (Universitas Tadulako, 2016)
Battery is one of a source of energy. Increasing the need of energy affects to the diminishing reserves of fossil energy sources. Therefore, this needs for energy sources alternative. Modification of chitosan-polyvinyl alcohol electrolyte membrane added with lithium salt has an advantage on environmentally friendly. This research aims to study the effect of adding percent weight of silica on the conductivity of the electrolyte polymers made from chitosan-polyvinyl alcohol-lithium. The ionic conductivity of the electrolyte polymer chitosan-polyvinyl alcohol-lithium-silica was measured by impedance spectroscopy. The results showed the electrolyte polymer with the addition of 5% silica performed the highest ionic conductivity by 2.005 x 10-7 S/cm. Characteristic of battery made from electrolyte polymer chitosan-polyvinyl alcohol-lithium with the addition of silica performed voltage of 1.5 Volts which was comparable to the commercial battery with the voltage of 1.8 Volts. These results indicate that silica can be used as a filler to improve the ionic conductivity.